Effect of Kinetin on Spruce Seed Germination - Singh, Virendra (Indian Forester, 1992)
Spruce seed was treated with different concentrations of kinetin solutions for different duration of soaking at room temperature. The highest germination percentage, was obtained by treating the seed with 1.5Ã—10-5 concentration of the solution after 72 hours of soaking.